The Survey of dermatophytic fungal infections in Thi-Qar proviance - Hashim Al-Yasiri, Mohammed; Alhuchami, Ahmed A.; Atiyah, Saad A. (Journal of Pakistan Association of Dermatologists, 2023)
Dermatophytoses spread world wide and caused by pathogenic filamentous fungi which infect skin, hair, and nails. The study aimed to determine the frequency and state of skin fungal infections in Nasiriyah city/South of Iraq. The samples under study were including: hair, Skin and nail fragments that collected from 500 patients with suspected dermatophytosis from private clinics in Al- during 2021, Fungal infections were detected according to standard diagnostic techniques. Dermatophytes infection was detected in 51 patients (10.2%), the frequency of Dermatophytes was higher in males (68.63%) than females (31.37%), the incidence of fungal infection was 64.71% in urban areas, when compared with rural areas, fungal infection in the scalp (tinea capitis) was more frequent, followed by face and arm of the patient’s body. In brief, fungal skin infections have high frequency among dermatological diseases especially in male and urban area with high frequency of tinea capitis infection.